Bioengineered three-dimensional scaffolds to elucidate the effects of material biodegradability on cell behavior using POSS-PEG hybrid hydrogels. (June 2019) - Li, Heling; Liu, Chungeng; Xu, Qi; Lu, Cuifen; Yang, Guichun; Wang, Feiyi; Nie, Junqi; Hu, Xingjian; Dong, Nianguo; Shi, Jiawei
Abstract: Tissue-engineered three-dimensional (3D) scaffolds are required to have a suitable degradation period and biocompatibility. Polyhedral oligomeric silsesquioxane−poly(ethylene glycol) (POSS−PEG) hybrid hydrogels with different degradation rates were prepared by varying the proportion of two cross-linkers, namely degradable PEG-diester-dithiol and non-degradable PEG-dithiol. These hydrogels were used as 3D scaffolds for the encapsulation, culture, and differentiation of cells to elucidate the effects of material biodegradability on cell behavior. Human umbilical vein endothelial cells (HUVECs) encapsulated in the 3D hybrid hydrogels were round-shaped with a cell survival rate of 98%. As the content of degradable cross-linker in the hybrid hydrogels was increased, the number of cells increased more rapidly, and the cell morphology gradually changed from slender spindle to round. Bone marrow mesenchymal stem cells (BMSCs) encapsulated in the 3D hybrid hydrogels grew and proliferated in both osteogenic differentiation media and cell culture growth media. As the content of the degradable cross-linker was increased, the osteogenic differentiation gradually increased, as indicated by the presence of calcium nodes. These results demonstrate that the degradation rates of the hybrid hydrogels had an effect on cell compatibility, morphology, and differentiation. Highlights: POSS-PEG hybrid hydrogels with different degradation rates were prepared by varying the proportion of two cross-linkers. The hybrid hydrogels were used as 3D scaffolds to elucidate the effects of material biodegradability on cell behavior. The degradation rates of the hybrid hydrogels had an effect on cell compatibility, morphology, and differentiation.